SEKTOR PARIWISATA DI PULAU NIAS - Helmut Weber (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1996)
The tourist potential in the island of Nias like the Langundri beach and Sorake have doubtlessly made it a place with a very high value from the stand point of tourist activities. This tourist potential has however, not yet beenfully exploited because the natural resource management and the human resource management is evidently still very limited. The greenness of the tourist potential in the island of Nias has got a strong attracting force towards the tourists from 11 source countries, including Germany. Because of this therefore, it is absolutely essential to formulate a strategy which can be used to develop tourism in this location, so that the place can improve on its position in the international market and also be able to improve on the welfare of the population here.Helmut Weber in his paper portrays the tourist potential in the island of Nias not only from the view point of its beautiful natural resources, but also from the angle of the rich cultural aspect of the community in this place which is very interesting to be enjoyed.